49th parallel [videorecording (DVD)] - Powell, Michael, 1905-1990; Howard, Leslie, 1893-1943; Olivier, Laurence, 1907-1989; Massey, Raymond; Walbrook, Anton, 1896-1967; Portman, Eric, 1901-1969; Johns, Glynis; Vaughan Williams, Ralph, 1872-1958 (Criterion collection, 2007)
As the voice over proclaims, the 49th parallel is the only undefended frontier in the world. The parallel is the goal of a small group of Nazi's, survivors of a U-boat that has been spotted and sunk in Hudson Bay, deep in Canadian waters. The United States is not yet at war with Germany, and if Corporal Hirth and his six crew members can reach it, they can be repatriated to Germany with no fuss. But their trek across Canada becomes a fierce struggle to survive, as they encounter and are opposed in turn by Johnnie the trapper, a small Hutterite community, a Canadian intellectual, and a Canadian soldier gone AWOL.